Phytochemical Composition, Antifungal and Antioxidant Activity of Duguetia furfuracea A. St.-Hill. (5th April 2016) - Pinho, Francisca Valéria Soares de Araújo; da Cruz, Litiele Cezar; Rodrigues, Nathane Rosa; Waczuk, Emily Pansera; Souza, Celestina Elba Sobral; Coutinho, Henrique Douglas Melo; Costa, José Galberto Martins da; Athayde, Margareth Linde; Boligon, Aline Augusti; Franco, Jeferson Luis; Posser, Thaís; de Menezes, Irwin Rose Alencar
Abstract : Background. Duguetia furfuracea is popular plant used in popular medicine. Hypothesis/Purpose. This claim evaluated the phytochemical composition of the hydroethanolic extract (HEDF), fractions of Duguetia furfuracea, and antioxidant and antifungal activity. Methods. The chemical profile was carried out by HPLC-DAD. The total phenolic contents and flavonoid components were determined by Folin-Ciocalteu and aluminium chloride reaction. The antioxidant activity was measured by scavenging of 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical and ferric reducing ability of plasma (FRAP) methods. The antifungal activity was determined by microdilution assay. Results. HPLC analysis revealed caffeic acid and rutin as major compounds (HEDF), caffeic acid and quercitrin (Mt-OH fraction), and quercitrin and isoquercitrin (Ac-OEt fraction). The highest levels of phenols and total flavonoids were found for Ac-OEt fraction, and the crude extract showed higher in vitro antioxidant potential. The antifungal activity showed synergic effect with fluconazole and EHDF against C. krusei, fluconazole and Mt-OH against C. krusei and C. tropicalis, and Ac-OE and fluconazole against C. albicans . Conclusion. The highest levels of phenols and total flavonoids were marked with antioxidant effect. This is the first report of bioactivity of the synergic effect of HEDF and fractions. More studies would be required to better clarify its mechanism of synergic action.